Information literacy as a basic skill in information society - Galewski, Tomasz (Publishing House of the Wrocław University of Economics, 2009)
Information literacy is a very important skill because we are living in a world which contains abundance of ways of getting information. In the new stage of economic and social development called “information society,” there is no problem not having enough information, it is just the opposite – too much information. We are bombarded with a constantly increasing amount of information, and such a high rate of growth has never been experienced before. This increasing problem of large quantities of information in life is generally called information overload. “There is no universally agreed upon definition of information overload – it can mean several things, such as having more relevant information than one can assimilate or being burdened with a large supply of unsolicited information, only some of which may be relevant” [Galewski, Kuśmierczyk 2008]. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 164-171